Prevalence and clinical aspects of mild cognitive impairment in Parkinson's disease: A meta‐analysis - Baiano, Chiara; Barone, Paolo; Trojano, Luigi; Santangelo, Gabriella (Movement disorders, 2020)
Mild cognitive impairment associated with Parkinson's disease (PD) is a risk factor for the development of dementia. Despite the importance of early identification of mild cognitive impairment in PD, its prevalence and clinical correlates are still debated. The present meta‐analysis provides a robust estimate of prevalence rate of mild cognitive impairment in PD according to the Movement Disorder Society clinical criteria and to explore the differences between PD patients with and without mild cognitive impairment in demographic, clinical, and neuropsychiatric features. A systematic literature search was performed up to April 2019 using PsycInfo (PROQUEST), PubMed, and Scopus. From 4706 titles and s, 41 studies were selected (n = 7053 patients). Pooled mild cognitive impairment prevalence was 40% on a total sample of 7053 PD patients (95% confidence interval = 36–44; Q = 490.14, P < 0.0001; I2 = 91.84%) with a higher frequency for the multiple domain subtype (31%; 95% confidence interval = 23–41, Q = 93.24; P < 0.0001; I2 = 92.49%). Meta‐regression analysis revealed that stage of PD moderate prevalence estimates of mild cognitive impairment (β = 2.80; P = 0.008). Mild cognitive impairment in PD was associated with older age, lower education, longer disease duration, higher levodopa equivalent daily dose, more severe motor symptoms, and postural instability/gait difficulty motor subtype, poorer quality of life, higher levels of apathy, and depression. The present meta‐analysis indicated that mild cognitive impairment in PD is a frequent cognitive status deserving to be early detected by means of standardized cognitive assessments in clinical practice. © 2019 International Parkinson and Movement Disorder Society